Vector of Malaria Receptivity Mapping at Melolo Health Center, Umalulu District, East Sumba Regency - Nelly Haryanty; Mursyid Raharjo; Yusniar Hanani (Postgraduate, University of Mataram, 2025)
Malaria is a life-threatening global infectious disease, which is spread through the bite of an infected female Anopheles mosquito. Plasmodium as the cause of malaria consists of six species, namely P. falciparum, P. vivax, P. malariae, P. ovale curtisi, P. ovale wallikeri, and P. Knowlesi. Indonesia is one of the malaria-endemic countries, with most of the districts/cities with high endemic status located in Papua and West Papua. East Nusa Tenggara Province still has three districts with high endemic status, namely East Sumba, West Sumba, and Southwest Sumba. In 2022, the number of laboratory-confirmed malaria cases in Indonesia reached 3,358,447 cases, an increase of 3.1% compared to 2021, which recorded 2,040,229 cases. This study aims to determine the pattern of malaria vector receptivity mapping in the Melolo Health Center Working Area, Umalulu District, East Sumba Regency. The type of research used is a descriptive approach. The results of the study showed that the level of malaria vector receptivity in the area was relatively high. The most common habitat found was swamps, with the most malaria sufferers being women aged between 6 and 50 years. The distribution pattern of malaria sufferers showed a cluster form, and the Malaria Habitat Index (IHM) value of 43.48% indicated the potential for significant spread of malaria.